Total cost of crude oil ownership for South African oil refiners - Bageloo, Kiren (My University, 2012)
The modern world is dependent upon the continuous production of liquid fuels, most of which are derived from crude oil. South Africa has very limited reserves of crude oil, which means that the five oil refineries located within its borders have to import most of their requirements. Adding this to the fact that fuel prices are regulated in South Africa and that oil refining is a low margin business, it then becomes evident that these companies have to do as much as they can to keep costs low in order to optimise profits. One of the tools that can assist managers in oil refineries in identifying points of leverage in procuring crude oil, is a total cost of ownership (TCO) analysis. The literature review highlighted that TCO studies, a form of activity based costing (ABC), is more complex than traditional costing methods, which hinders it use and affects its trustworthiness in practice. Furthermore, it was found that there is a trade-off between complexity and accuracy. The aim of this research was to identify the elements of crude oil TCO for a South African oil refinery and the accuracy and precision thereof. The method of data collection was via semi-structured interviews and archival data retrieval. The aim was firstly to determine how the TCO was calculated in the chosen organisation, and then to use the information from the semi-structured interviews and archives to determine the actual TCO. This was then used to determine the accuracy of the TCO analysis done by the chosen company. It was found in this study that the accuracy of the indirect cost element of the TCO was only 78% and had a higher standard deviation than the actual costs. The conclusion is that although this level of accuracy compares to other studies done in practice, there is still room to improve the reliability of current crude oil TCO analyses that are carried out in the chosen organisation, simply due to the high value of crude oil. Given that there is a correlation between improvement in ROI and the use of ABC methods, the conclusion is that more accurate TCO studies are important for low margin businesses such as oil refining.
MBA thesis - WBS
Keywords: Crude oil ownership; Refineries, Oil; Oil refineries